Мовна репрезентація кульмінаційного моменту в німецьких новелах ХХ століття - Кравченко, Н.Г. (Лінгвістика ХХІ століття: нові дослідження і перспективи, 2010)
В статье проанализировано определение новеллы как жанра немецкой прозы. Определены ключевые тенденции ее развития в ХІХ-ХХ ст., установлены основные особенности ее структурного построения и использованных средств экспрессивности. In the article the definition of the short story as a German prose genre has been analysed. The basic trends of its development in the nineteenth and twentieth centuries are defined, as well as the basic peculiarities of its structural construction and use of expressive means.